2002
DOI: 10.5694/j.1326-5377.2002.tb04699.x
|View full text |Cite
|
Sign up to set email alerts
|

High bone turnover in Muslim women with vitamin D deficiency

Abstract: CHRONIC VITAMIN D DEFICIENCY may lead to osteomalacia and/or osteoporosis, with an increased risk of fragility fractures. 1 In Australia, with its multicultural population, a resurgence of vitamin D deficiency has been noted recently. 2 While there are reports of abnormalities in vitamin D metabolism in Muslim women, 3,4 there are no published data on fracture rates, bone mass measurements or bone turnover rates in this cohort. We aimed to determine the effect of vitamin D deficiency on bone turnover in Muslim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…Garnero et al [35] have indicated that vitamin D is unlikely to play a major role in regulating the systemic levels of bone turnover markers. In the present study, as reported in several previous studies [36], [37], we found a significant inverse correlation between the serum levels of 25(OH)D and bone turnover markers, independent of age and BMI. These data suggest that vitamin D insufficiency may be related to accelerated bone turnover, and subsequently, osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…Garnero et al [35] have indicated that vitamin D is unlikely to play a major role in regulating the systemic levels of bone turnover markers. In the present study, as reported in several previous studies [36], [37], we found a significant inverse correlation between the serum levels of 25(OH)D and bone turnover markers, independent of age and BMI. These data suggest that vitamin D insufficiency may be related to accelerated bone turnover, and subsequently, osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…Five articles provided descriptive information on African or refugee medical and physical health derived from on-arrival screening or related services [30-34]; three discussed Vitamin D deficiency in veiled and dark-skinned women and their babies [35-37]; five were concerned with the mental health of refugees [15,38-41]; one with iron depletion in Arabic-speaking toddlers [42]; one examined the hospital utilisation of refugees based on their source country [43]; one examined the differential access rights of Temporary Permit Visa holders, as compared with refugees [44]; one studied the primary care utilisation patterns of 341 asylum seekers in Melbourne [45]; one studied the effectiveness of outpatient malarial treatment with African refugees [46]; one looked at the barriers to healthcare access for newly arrived African refugees [47]; one studied shared antenatal care by women of non-English speaking backgrounds [16]; and one studied the positive relationship between intravenous drug use and Human Immunodeficiency Virus in Indochinese communities [48]. …”
Section: Resultsmentioning
confidence: 99%
“…Low level of vitamin D has been reported in the adult population of Malaysia [16], China [17], Thailand [18], Korea [19], and India [20, 21]. A study in Australia reported the high prevalence of vitamin D deficiency among the Australian Muslim healthy women [22]. Vitamin D containing food like high intake of fish, fortification of food with vitamin D, or supplementation of vitamin D may be the causes of these differences.…”
Section: Discussionmentioning
confidence: 99%